United States menhaden oil could save billions in U.S. health care costs and improve IQ in children. Issue 2 (February 2016) - Bibus, Douglas M.
Abstract : The United States menhaden oil annual production is sufficient to supply all of the recommended long chain Omega‐3s for Americans over 55 with coronary heart disease (CHD) and pregnant and lactating women. According to a recent study, the utilization of preventable intake levels could potentially save up to $1.7 billion annually in hospital costs alone. In addition, the remaining oil could be used to support a culture of enough Atlantic salmon to provide every pregnant and lactating woman in the U.S. with 8‐12 ounces of fish per week, as recommended by the Food and Drug Administration (FDA), throughout the duration of pregnancy and lactation. Based on the FDA's quantitative assessment, this may result in a net increase of IQ by 5.5 points in children and improve their early age verbal development.